(untitled) (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2010)
Pulp degradation during cocoa fermentation can be carried out by depolymerization process of pulp pectin using endogenous pectolytic enzymes at optimum condition. The objectives of this research were to study the effect of fermentation process based on optimum condition in terms of temperature and pH of pulp pectin depolymerization using endogenous pectolytic enzymes polygalakturonase (PG) and pectin metyl esterase (PME) and fermentation period in cocoa processing on quality characteristics of cocoa beans produced and to study the role of those fermentation process in reducing fermentation time to produce cocoa beans with standard quality. This research used split plot design, with treatments of process condition of cocoa fermentation as main plot and fermentation period as split plot. Treatment of process condition of cocoa fermentation consisted of optimum condition for pulp pectin depolymerization by PGs (temperature 47.5OC; initial pulp pH 4.6); optimum condition of depolymerization on sequence depolymerization by PGs (temperature 48.5OC; initial pulp pH 8.0 during 1 day; last temperature 47.5OC; initial pulp pH 4.6 during 6 days), and natural fermentation process a control. While treatment of fermentation period consisted of 0, 1, 2, 3, 4, 5, 6 and 7 days. Evaluation of fermentation period was carried out based on pursuant to criteria of unfermented beans content and fermentation index. The results showed that process condition and fermentation time of cocoa affected quality characteristic of cocoa beans produced. Period of cocoa fermentation process based on optimum condition for pulp pectin depolymerization using endogenous pectolytic enzymes was 2 days shorter compared to natural fermentation. Cocoa beans quality of grade I and II were obtained from fermentation time of 4 and 2 days, respectively, using fermentation process based on optimum condition of pulp pectin depolymerization using endogenous pectolytic enzymes, whereas 6 and 4 days, respectively, when using natural fermentation. Key words: cocoa quality, fermentation, depolymerization, pectolytic.